Neurosteroids: a lifelong impact on brain health - Walton, Najah L.; Maguire, Jamie L. (Frontiers in Behavioral Neuroscience, 2025)
Neurosteroids are critical regulators of brain function, exerting profound effects on neurodevelopment, emotional regulation, cognition, and resilience to stress across the lifespan. Synthesized endogenously in the brain and peripheral tissues, neurosteroids modulate neural circuits through both genomic and non-genomic mechanisms. This review synthesizes current evidence on the roles of neurosteroids from fetal development through advanced biological aging, emphasizing their involvement in neuronal plasticity, synaptic modulation, myelination, and neurogenesis. We explore how neurosteroid dysregulation contributes to mood and cognitive disorders and highlight age- and sex-related changes in neurosteroid synthesis which may impact risk. Lifestyle factors including diet, exercise, and mindfulness are also examined for their ability to modulate neurosteroidogenesis and promote brain health. By integrating findings across developmental stages and physiological states, we underscore the functional roles of neurosteroids as modulators of emotional and cognitive states across the lifespan, and advocate for deeper investigation into neurosteroid-based intervention for across indications and throughout the lifespan.